Determinants of capital structure in Sharia criteria manufacturing firms on the Indonesia Stock Exchange - Muhamad Umar Mai (University of Merdeka Malang, 2019)
Theories and results of research on the determinants of a firm’s capital structure provide different explanations and evidence. Sharia criteria companies on the Indonesia Stock Exchange (IDX) are not allowed to have a ratio of total interest-based debt to total assets of more than 45%, which predicted have an impact on the determinants of their capital structure. This research was conducted at Sharia criteria manufacturing companies on the Indonesia Stock Exchange in 2011-2017. The results of the analysis showed that only profitability had the same direction that is negative on the two capital structure measures, book leverage and market leverage. Growth opportunity and firm size have different effects on the two capital structure measures, which are a positive effect on book leverage and negative on market leverage. Tangibility, business risk, and inflation only affect market leverage. Tangibility and inflation have a positive effect on market leverage, while business risk has a negative effect. This study found no evidence that gross domestic product (GDP) affects leverage, both on book leverage and market leverage.JEL Classification: C12, C33, E22, E52, G32DOI: https://doi.org/10.26905/jkdp.v23i3.1860